Dynamic microscopic analysis method for evaluating dispersing performance of nano calcium carbonate powder

Through dynamic microscopic analysis method, nano calcium carbonate powder is treated by spraying and ultrasonic oscillation, and its dispersion rate is calculated, which solves the accuracy and timeliness of dispersion performance evaluation in the prior art, and achieves efficient and accurate dispersion performance evaluation.

CN119845798APending Publication Date: 2025-04-18JIANDE TIANSHI CALCIUM CARBONATE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411913204.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to objectively, accurately and efficiently evaluate the dispersion performance of nano calcium carbonate powders, especially in production application scenarios, with low testing accuracy, poor reproducibility, complex operation and poor timeliness.

Method used

Using dynamic microscopic analysis method, the geometric dimensional change rate of particles or clusters is observed and calculated to evaluate their dispersion rate and dispersion performance by spraying nano calcium carbonate powder onto the carrier film and performing ultrasonic oscillation treatment.

Benefits of technology

The dispersion performance of nano calcium carbonate powders is quickly and accurately evaluated at the production site, and the test results are visualized, dynamic and quantitative, with high resolution and accuracy, and good reproducibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845798A_ABST
    Figure CN119845798A_ABST
Patent Text Reader

Abstract

The invention discloses a dynamic microscopic analysis method for evaluating the dispersing performance of nano calcium carbonate powder. The dynamic microscopic analysis method comprises the following steps: A, fixing a carrier film on a glass slide; b, mixing nano calcium carbonate powder to be detected in fluid, and spraying the fluid on the carrier membrane; c, carrying out ultrasonic oscillation treatment on the carrier film and the glass slide together; d, respectively observing the distribution states of the nano calcium carbonate powder on the carrier film before and after the ultrasonic treatment by using a microscope, and capturing a stably imaged picture; e, processing the picture obtained in the step D by using a computer processing program, marking representative nano calcium carbonate particles or clusters, counting the geometric dimensions (maximum dimension) of the nano calcium carbonate particles or clusters, and solving the average geometric dimensions D0 and Dt respectively; and F, calculating the dispersion rate (Dt-D0) / t of the nano calcium carbonate powder, so as to evaluate the dispersion performance of the nano calcium carbonate powder. The scheme has the beneficial effects that the dispersing performance of the nano calcium carbonate can be quickly and accurately evaluated under the condition close to an actual application scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of particle characteristic testing, in particular to a dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder. Background Art

[0002] Nano calcium carbonate is an inorganic non-metallic material with large resource reserves, high cost performance and environmental friendliness. It is widely used as a filler, reinforcing agent or carrier in rubber filling, plastic modification, new material synthesis and health. No matter what the application field or scenario, nano calcium carbonate is first required to have good dispersibility, that is, the powder particles and their clusters are quickly integrated into the medium and dispersed into small, stable discrete particles.

[0003] Since the original size of nano calcium carbonate is less than 100 nanometers, the surface energy is large and the thermodynamics is unstable, the powder particles tend to spontaneously agglomerate under the action of van der Waals force, liquid bridge force and electrostatic force to form micron-sized clusters to reduce the surface energy, that is, to obtain a stable state by sacrificing the nanoscale and reducing the dimension; secondly, the mainstream synthesis route of nano calcium carbonate is carbonation-wet modification or modification-solid-liquid separation-drying and crushing. This process includes multiple nanoparticle dispersion-agglomeration-redispersion processes. Each redispersion cannot guarantee that the macroscopic hard particles formed by the previous agglomeration are refined to the meso-micro scale again. Therefore, objectively evaluating the actual dispersion performance of nano calcium carbonate powder has become a common focus of attention for upstream and downstream industries.

[0004] At present, the main methods for evaluating the dispersibility of nano-calcium carbonate powder in the industry include coating method, scraper fineness method, laser particle size method, Zeta potential method, electron microscope method, etc. The coating method qualitatively judges the dispersibility of the powder by observing the brightness and flatness of the nano-calcium carbonate mixture coating, which is greatly affected by the ambient light and the subjective influence of the tester; the scraper fineness method, similar to the coating method, indicates the fineness or particle size of the powder by measuring the position where the scratch appears after the mixture is coated, which mainly reflects the scale of hard particles and is invalid for the scale of soft clusters; the laser particle size method characterizes the dispersibility by testing the particle size distribution of the powder, but the test object is only the scale of the secondary cluster structure, which cannot fully reflect the dispersibility; the Zeta potential method: from the electrochemical point of view, the size of the mutual repulsion or attraction of particles in the medium is measured to characterize the dispersibility, but the theoretical correlation between the surface energy and the dispersibility is not yet mature, and the test conditions and operation process are complicated. It is currently used for theoretical research and cannot be used for on-site analysis. The electron microscopy method directly observes the crystal morphology and particle state of nano-calcium carbonate powder through a scanning electron microscope or a projection electron microscope to judge the dispersion. It is limited by the narrow observation field, low sample representativeness, poor timeliness and other reasons, and is not suitable for daily analysis, evaluation and quality control of production enterprises.

[0005] The Chinese patent document CN118670935A disclosed on September 20, 2024, "Double-slot scraper fineness meter and method for detecting the hiding power of titanium dioxide in coatings", which discloses a double-slot scraper fineness meter, including a scraper fineness meter body, which is equipped with a pair of detection slots, one of which has a black background color and the other has a white background color. The invention also discloses a method for detecting the hiding power of titanium dioxide in a coating by using a double-slot scraper fineness meter, which uses the double-slot scraper fineness meter as described above, and includes the following steps: (1) preparing a titanium dioxide slurry sample to be tested; (2) performing scraper readings on the titanium dioxide slurry sample on the double-slot scraper fineness meter to determine the dispersibility of the titanium dioxide slurry sample; (3) placing the double-slot scraper fineness meter on a table after reading, waiting for the titanium dioxide slurry sample to form a film and dry naturally; (4) observing the position where the color difference first appears in the two detection slots, reading the slot depth at that position, and taking the slot depth as the hiding power of the titanium dioxide slurry sample. This scheme is a typical scraper method.

[0006] From the above, it can be seen that the existing methods for evaluating the dispersion performance of nano-calcium carbonate have some defects in both theory and operation. It is difficult to objectively, accurately and efficiently characterize the actual dispersion performance of nano-calcium carbonate powder in production application scenarios. It is urgent and necessary to develop more reliable and efficient analysis and evaluation methods. Summary of the invention

[0007] Based on the above problems, the present invention provides a dynamic microscopic analysis method for quickly characterizing the dispersion properties of nano-calcium carbonate powder, which solves the problems commonly existing in existing nano-calcium carbonate dispersion performance analysis methods, such as low correlation between testing and production application, low test accuracy, poor reproducibility, complex operation, poor timeliness, and difficulty in meeting the requirements of industrial production site testing.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical scheme: a dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder comprises the following steps: A, fix the carrier membrane on the slide; B, mixing the nano calcium carbonate powder to be tested in a fluid and spraying the mixture on the carrier film; C, subjecting the carrier film and the glass slide to ultrasonic vibration treatment together; D. Use a microscope to observe the distribution state of nano-calcium carbonate powder on the carrier membrane before and after ultrasonic treatment, and capture stable imaging pictures; E. Process the image obtained in step D using a computer program, mark representative nano-calcium carbonate particles or clusters, count their geometric dimensions (maximum dimension), and obtain the average geometric dimensions D0 and D t ; F, calculate the dispersion rate of nano calcium carbonate powder (D t-D0) / t, in order to evaluate its dispersion performance.

[0009] Preferably, a fluidizing device is used in step B, and the fluid is compressed air.

[0010] Preferably, the spraying direction of the fluidizing device is perpendicular to the plane where the glass slide is located.

[0011] Preferably, the nozzle pressure of the fluidization device is 1-3 MPa, the flow rate is 4-6 L / min, the initial velocity is 10-15 m / s; and the distance from the nozzle to the glass slide is 5-10 mm.

[0012] Preferably, the fluidizing device adopts a pulse spraying method, and the pulse spraying time is 30 to 50 ms.

[0013] Preferably, in step C, the carrier film and the glass slide are placed horizontally in a sample boat, and the sample boat floats on the surface of the medium water in the ultrasonic generator.

[0014] Preferably, the ultrasonic oscillation treatment time is 30-60s.

[0015] Preferably, the carrier membrane material is determined by the polarity of the downstream application system.

[0016] Preferably, the carrier film is a silica gel film or a polyethylene film.

[0017] Preferably, the carrier film and the glass slide are bonded together with DOP.

[0018] Existing nano-calcium carbonate products are mainly powder products with organic surface modification. The filling or reinforcing effects must be achieved through dispersion and adsorption to the substrate interface. Therefore, the dispersion process and adsorption behavior of nano-calcium carbonate powder on the substrate interface can be investigated, and the geometric size and dispersion differences of nano-calcium carbonate clusters adsorbed on the substrate interface (polar or non-polar) can be measured to characterize and evaluate the quality of its dispersion. Generally speaking, as the dispersion time increases, the nano-calcium carbonate clusters gradually disintegrate, the geometric scale gradually decreases, the proportion of the dispersed phase in the substrate increases, and the dispersion is more sufficient. Based on the above analysis, we combined the ultrasonic dispersion technology of nano-powders with microscopic imaging technology, and defined the dispersion rate by the rate of change of the cluster scale reduction over time v: -dD / dT (unit: μm / s) by observing and measuring the disintegration process of nano-calcium carbonate powder clusters on polar or non-polar interfaces and the scale reduction rate. The higher the dispersion rate, the faster the dispersion process of the nano-calcium carbonate clusters and the better the dispersion. According to the above analysis, the following formula can be obtained: That is, the formula in step F above (D t -D0) / t In the formula, D: average diameter of nano-calcium carbonate clusters, in μm; D t : average diameter of nano-calcium carbonate clusters at dispersion time t, in μm; D0: average diameter of nano-calcium carbonate clusters at dispersion time 0, in μm; T t : The moment of complete dispersion, unit s, T t >T0; T0: the time of first observation, unit: s, 0s≤T0≤30s.

[0019] In the aforementioned steps, spraying represents adsorption and oscillation represents dispersion, thereby completely simulating the polymerization and dispersion process of nano-calcium carbonate under actual application conditions.

[0020] The beneficial effects of this solution are: 1. The test device and operation are relatively simple, suitable for on-site analysis and testing; 2. The analysis process is visualized, dynamic and quantitative, which can intuitively reflect the dynamic process and results of the dispersion of nano-calcium carbonate particles; 3. Different carrier membranes can be flexibly selected according to the application system, and the test is highly targeted; 4. The resolution and accuracy are high, and the results are reproducible. In summary, the method of the present invention can quickly and accurately evaluate the dispersion performance of nano-calcium carbonate under conditions close to actual application scenarios, and has a more direct guiding role in the production activities of upstream and downstream industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : Schematic diagram of the theoretical basis of the nano-calcium carbonate dispersibility analysis method; Figure 2 : Microscopic image of the dispersion of nano-calcium carbonate sample on silica gel membrane; Figure 3 : Microscopic image of nano calcium carbonate powder (NPCC1) on silica gel membrane in Example 1; Figure 4 : Microscopic image of nano calcium carbonate powder (NPCC2) on silica gel membrane in Example 1; Figure 5 : Microscopic image of nano calcium carbonate powder (NPCC3) on silica gel membrane in Example 1; Figure 6 : Microscopic image of nano calcium carbonate powder (NPCC4) on silica gel membrane in Example 1; Figure 7 : Microscopic image of nano calcium carbonate powder (NPCC1) on polyethylene film in Example 2; Figure 8 : Microscopic image of nano calcium carbonate powder (NPCC2) on polyethylene film in Example 2; Fig. 9 : Microscopic image of nano calcium carbonate powder (NPCC2) on silica gel membrane in Example 3; Fig.10 : Microscopic image of nano calcium carbonate powder (NPCC2) on polyethylene film in Example 4; Fig.11 : The scraper fineness image of the nano calcium carbonate powder dispersed in silica gel in Comparative Example 1; Fig.12 : Particle size distribution diagram of nano calcium carbonate powder obtained by laser particle size test in Comparative Example 2; Fig.13 : The image obtained by scanning electron microscope analysis of nano calcium carbonate powder in Comparative Example 3; Fig.14 : Optical microscopic image of the nano calcium carbonate / silica gel mixture coating in Comparative Example 4. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0023] For the convenience of comparison, the embodiments and comparative examples used nano-calcium carbonate samples to be tested prepared by the same process and having different index characteristics for subsequent comparative experiments: Table 1: Relevant data of the nano calcium carbonate samples to be tested Note: 1) BET (m 2 / g) was measured by T / ZZB 2328-2021 method using 3H-2000A BET analyzer; 2) the amount of modifier was determined by thermal gravimetric method (400°C, 2h); the oil absorption value was tested by national standard GB / T19281-2003 method; the apparent viscosity was measured by T / ZZB 2328-2021 method using RVDV-s rotational viscometer.

[0024] The operation steps of the embodiment are generally described as follows: First of all, there are multiple options for the carrier film used in the spraying process, but it should meet two principles: first, it should be thin and flat and can be fixed on a glass slide; second, the material of the carrier film is determined by the polarity of the downstream application system. For example, if it is used in a polar system such as silicone rubber, it is recommended to choose a silicone film. If it is used in a non-polar polymer system such as polyethylene plastic, it is recommended to choose a polyethylene film.

[0025] The steps for preparing the silica gel membrane are given below: Weigh 30g of 107 glue, put it into a vacuum dryer at 150℃ for 10min; after cooling to 60℃, add 3g of cross-linking agent and stir thoroughly, then drop 0.3g of catalyst and stir quickly, quickly pour it into a mold and press it into a silicone mold, and cure it for 7 days until it is completely cross-linked and cured.

[0026] The steps for preparing polyethylene film are given below: Mix equal masses of linear polyethylene resin 8320 and low-density polyethylene resin M1850 evenly, dry at 100°C for 10 minutes, then pour into the film blowing machine, adjust the extrusion screw speed, traction speed and blower air volume, start film blowing, and cut a transparent and uniform film after the operation is stable.

[0027] The silicone film or polyethylene film can also be purchased as commercially available products that meet the requirements. For example, the polyethylene film can be replaced by a commercially available PE cling film with a thickness of 10 to 20 μm.

[0028] There are many ways to fix the carrier film, so as to facilitate the attachment of the sprayed powder and not affect the optical observation. If it is to fit, DOP can be used as an adhesive to stick the carrier film to the upper surface of the slide. DOP is dioctyl phthalate, which is a common plasticizer. It is colorless and transparent and does not affect optical observation when used here. Those skilled in the art can also replace it with other materials that meet the conditions. It should be noted that in order to ensure good adhesion and observation effects, after the carrier film is affixed, it should be leveled before the adhesive is cured, such as rolling with a glass rod to ensure that the carrier film and the slide are tightly fitted, flat and free of bubbles.

[0029] Secondly, the fluidization device selected for spraying can refer to the "Fluidization device for homogenization of nano-calcium carbonate powder" disclosed in Chinese patent document CN216987991U on July 19, 2022. The structure can be simpler: the main body is a straight tube, the upstream air inlet is large, the downstream air outlet is small, and a feed port is provided on the side wall in the middle of the tube. Compressed air is introduced into the air inlet, and after being pressurized and accelerated by the fluidization device, it is ejected from the air outlet. The nano-calcium carbonate powder to be tested is added to the feed port, carried by the compressed air, and ejected from the air outlet in a direction facing the carrier film on the glass slide, so that the nano-calcium carbonate particles are sprayed and adsorbed on the surface of the carrier film.

[0030] If the fluidization device is not available, a simple alternative method can also be used: fix the carrier membrane on a glass slide, take a balloon dropper, load a small amount of nano-calcium carbonate powder to be tested at the nozzle, press the balloon to spray the air onto the carrier membrane, spray the nano-calcium carbonate powder on the surface of the carrier membrane at an angle, and then use a balloon dropper without nano-calcium carbonate powder to spray the air onto the surface of the carrier membrane to blow away the floating powder and only retain the powder adsorbed on the membrane surface.

[0031] Third, in the ultrasonic oscillation treatment stage, a sample boat is selected to carry the carrier film and the glass slide sprayed with calcium carbonate particles, and water is used as a medium to carry the sample boat, rather than directly oscillating the carrier film and the glass slide. The purpose of doing so is to utilize the moderate density and molecular flexibility of water to depolymerize and disperse the carrier film and the nano-calcium carbonate particles thereon. If the high-density solid carrier is directly subjected to ultrasonic oscillation, the ultrasonic anisotropy is significantly increased, the spatial stereoscopicity of the oscillation is reduced, and the energy dissipation is also accelerated, which may be unfavorable for the dispersion of the nano-calcium carbonate particles. Those skilled in the art can also select other suitable liquid media according to actual needs.

[0032] Fourth, during the optical observation stage of the microscope, it is recommended that the objective lens magnification of the optical microscope be 10-100, and the eyepiece magnification be 16. When observing, first use the 10x objective lens to find a clear imaging area, and then switch to a high-magnification objective lens. To meet the clarity requirements, the resolution of the captured image is recommended to be higher than 100dpi.

[0033] Fifth, in the computational image processing stage, it is recommended to select particles or clusters at more than five different locations and measure their long axis dimensions separately to eliminate randomness and make the results more objective and fair.

[0034] Figure 1 As shown, it is a schematic diagram of the theoretical basis of the nano-calcium carbonate dispersibility analysis method, which intuitively introduces the difference between the traditional scheme (upper right) and this scheme (lower right); Figure 2 Shown is a microscopic image of the dispersion of the nano-calcium carbonate sample on the silica gel membrane of this scheme.

[0035] According to the inventor's research results, the present invention adopts the dispersion rate to characterize the dispersion performance of nano-calcium carbonate powder particles in a specific medium. The higher the value, the faster the clusters disintegrate and reduce in size, and the better the dispersion.

[0036] Embodiment 1: Embodiment 1 is a dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder, which specifically comprises the following steps: 1. Cut the 30μm thick silicone film into a rectangular film slightly smaller than the glass slide, and vertically attach it to the glass slide with DOP to form a carrier film assembly. Then fix it at the fluidization nozzle, with the center of the carrier film facing the nozzle, and maintain a horizontal spacing of 10mm; 2. Load 1g of nano calcium carbonate powder with sample number NPCC1 into the feed port of the fluidizing device, adjust the pulse time to 45ms, and then start the fluidizing device to quickly spray the nano calcium carbonate powder onto the surface of the carrier film; 3. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 2, and capture a stable imaging picture such as Figure 3 As shown in the left figure; 4. Remove the carrier membrane assembly adsorbing nano-calcium carbonate powder from the microscope stage, place it horizontally in the sample boat in the ultrasonic generator, and start the ultrasonic generator for ultrasonic oscillation and dispersion for 60 seconds; 5. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 4, magnify it 640 times, and capture a stable imaging picture as shown below: Figure 3 As shown in the right figure; 6. Perform computer processing on the images obtained in steps 3 and 5, mark representative nano-calcium carbonate particles or clusters, count their geometric dimensions (maximum dimension), and obtain the average geometric dimensions D0 and D t ; 7. Calculate the dispersion rate V of nano calcium carbonate powder = (D t -D0) / t; 8. Repeat the above steps 3 times, and change the sample numbers to NPCC2, NPCC3 and NPCC4 in turn. Capture the stable imaging pictures in order as follows: Figure 4 , Figure 5 , Figure 6 shown.

[0037] Embodiment 2: Embodiment 2 is another dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder, which specifically comprises the following steps: 1. Cut a 15μm thick polyethylene film into a rectangular film slightly smaller than the glass slide, and vertically attach it to the glass slide with DOP to form a carrier film assembly; then fix it at the fluidization nozzle, with the center of the carrier film facing the nozzle, and maintain a horizontal spacing of 10mm; 2. Load 1g of nano calcium carbonate powder (sample number NPCC2) into the silo, adjust the pulse time to 50ms, and then start the fluidization device to quickly spray the nano calcium carbonate powder onto the surface of the carrier film; 3. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 2, and capture a stable imaging picture such as Figure 7 As shown in the left figure; 4. Remove the carrier membrane assembly adsorbing nano-calcium carbonate powder from the microscope stage, place it horizontally in the sample boat in the ultrasonic generator, and start the ultrasonic generator for ultrasonic oscillation and dispersion for 45 seconds; 5. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 4, magnify it 640 times, and capture a stable imaging picture as shown below: Figure 7 As shown in the right figure; 6. Perform computer processing on the images obtained in steps 3 and 5, mark representative nano-calcium carbonate particles or clusters, count their geometric dimensions (maximum dimension), and obtain the average geometric dimensions D0 and D t ; 7. Calculate the dispersion rate V of nano calcium carbonate powder = (D t -D0) / t; 8. Repeat the above steps once, and change the sample number to NPCC2, and capture the stable imaging picture as follows Figure 8 shown.

[0038] Embodiment 3: Embodiment 3 is another dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder, which specifically comprises the following steps: 1. Cut the 30μm thick silica gel film into a rectangular film slightly smaller than the glass slide, and vertically attach it to the glass slide with DOP to form a carrier film assembly; then fix it at the fluidization nozzle, with the center of the carrier film facing the nozzle, and maintain a horizontal spacing of 10mm; 2. Load 1g of nano calcium carbonate NPCC2 powder into the silo, adjust the pulse time to 30ms, and then start the fluidization device to quickly spray the nano calcium carbonate powder onto the surface of the carrier film; 3. Place the carrier membrane assembly adsorbing nano-calcium carbonate powder horizontally in the sample boat in the ultrasonic generator, and start the ultrasonic generator for ultrasonic vibration dispersion for 50 seconds; 4. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 3, magnify it 640 times, and capture a stable imaging picture as shown below: Fig. 9 As shown in the left figure; 5. Remove the carrier membrane assembly adsorbing nano-calcium carbonate powder from the microscope stage and disperse it by ultrasonic vibration for 60 seconds again; observe the distribution state of nano-calcium carbonate particles again, magnify it 640 times, and capture a stable imaging picture as shown below: Fig. 9 6. Perform computer processing on the images obtained in steps 4 and 5, mark representative nano-calcium carbonate particles or clusters, count their geometric dimensions (maximum dimension), and obtain the average geometric dimensions D0 and D t ; 7. Calculate the dispersion rate V of nano calcium carbonate powder = (D t -D0) / t.

[0039] Embodiment 4: Example 4 is another dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder, which specifically includes the following steps: 1. Cut the 15μm thick polyethylene film into a rectangular film slightly smaller than the glass slide, and vertically attach it to the glass slide with DOP to form a carrier film assembly. Then fix it at the fluidization nozzle, with the center of the carrier film facing the nozzle, and maintain a horizontal spacing of 10mm; 2. Load 1g of nano calcium carbonate powder into the silo, adjust the pulse time to 50ms, and then start the fluidization device to quickly spray the nano calcium carbonate powder onto the surface of the carrier film; 3. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 2, and capture a stable imaging picture such as Fig.10 As shown in the left figure; 4. Remove the carrier membrane assembly adsorbing nano-calcium carbonate powder from the microscope stage, place it horizontally in the sample boat in the ultrasonic generator, and start the ultrasonic generator for ultrasonic vibration and dispersion for 50 seconds; 5. Use an optical microscope to observe the distribution state of the nano calcium carbonate particles on the carrier film obtained in step 4, magnify it 640 times, and capture a stable imaging picture as shown below: Fig.10 As shown in the right figure; 6. Perform computer processing on the images obtained in steps 3 and 5, mark representative nano-calcium carbonate particles or clusters, count their geometric dimensions (maximum dimension), and obtain the average geometric dimensions D0 and D t ; 7. Calculate the dispersion rate V of nano calcium carbonate powder = (D t -D0) / t.

[0040] Comparative Example 1 This comparative example is a scraper fineness method for evaluating the dispersibility of nano calcium carbonate powder, which specifically includes the following steps: 1. Weigh (65±0.5) g of silicone rubber (commercially available RTV-107-2, viscosity (20000±2000) mPa.s) and nano calcium carbonate, add them into a clean 500 ml plastic beaker, and fix them on the base of the mixer; 2. Adjust the height of the mixer blade, immerse it vertically into the middle of the nano calcium carbonate-silica gel mixture, start stirring, first stir at a low speed of 100-150r / min for 5 minutes to allow the silicone rubber to fully infiltrate the nano calcium carbonate, and then stir the paste at a high speed of 550r / min for 10 minutes to obtain a uniform and delicate silicone rubber base material; 3. Use a glass rod to dip a proper amount of the silicone rubber base material obtained in step 2 and stick it on the top of the central groove of the scraper fineness gauge (range 0-100μm), slightly above 100μm; 4. Use a stainless steel scraper (provided with the fineness gauge) to quickly scrape the silicone rubber base material vertically from top to bottom until it is below the 0μm scale line; 5. Observe the scratches formed in the silicone rubber base coating in the groove of the fineness gauge, mark the initial position of the scratches, and record the corresponding value (μm); 6. Repeat the above steps 3 times, and change the sample numbers to NPCC2, NPCC3 and NPCC4 in turn. See the scraper fineness record pictures of the four specifications of samples for details. Fig.11 Shown from left to right in.

[0041] The finenesses of the four samples are: NPCC1 (14.8 μm), NPCC2 (65.0 μm), NPCC3 (81.8 μm), NPCC4 (79.9 μm), and the dispersion performance is ranked from high to low as: NPCC1>NPCC2>NPCC4>NPCC3.

[0042] Comparative Example 2 This comparative example is a laser particle size method for evaluating the dispersibility of nano calcium carbonate powder. The particle size test method in national standard GB / T19281-2003 is used to test the particle size of nano calcium carbonate samples. The results are as follows: Fig.12 As shown in the figure, the dispersion of the four samples was comprehensively judged based on the peak position of the particle size distribution, the distribution width and other information, and the order from high to low is: NPCC3>NPCC2>NPCC1>NPCC4.

[0043] Comparative Example 3 This comparative example is an electron microscopy method for evaluating the dispersion performance of nano calcium carbonate powder. The nano calcium carbonate sample is tested using the microscopic morphology test method in the national standard GB / T19281-2003. The results are as follows: Fig.13 As shown. According to the aggregation degree and cluster size of nano-calcium carbonate-like microscopic particles, NPCC4 particles are the smallest, almost all of which form obvious rod-shaped secondary cluster structures. A small number of NPCC1 particles are stuck together. The morphology and dispersion of NPCC2 and NPCC3 particles are not significantly different. Based on experience, their dispersion is comprehensively judged and ranked from high to low as follows: NPCC2>NPCC3>NPCC1>NPCC4.

[0044] Comparative Example 4 This comparative example is an optical imaging method for evaluating the dispersibility of nano calcium carbonate powder, which specifically includes the following steps: 1. Weigh (65±0.5) g of silicone rubber (commercially available RTV-107-2, viscosity (20000±2000) mPa.s) and nano calcium carbonate, add them into a clean 500 ml plastic beaker, and fix them on the base of the mixer; 2. Adjust the height of the mixer blade, immerse it vertically into the middle of the nano calcium carbonate-silica gel mixture, start stirring, first stir at a low speed of 100-150r / min for 5 minutes to allow the silicone rubber to fully infiltrate the nano calcium carbonate, and then stir the paste at a high speed of 550r / min for 10 minutes to obtain a uniform and delicate silicone rubber base material; 3. Use a glass rod to spread the silicone rubber base obtained in step 2 on a glass slide to form a uniform film.

[0045] Observe the size and distribution of nano-calcium carbonate particles or clusters in the film in step 3, and compare and qualitatively analyze the dispersibility of nano-calcium carbonate particles. The results are as follows: Fig.14 The four samples all formed a certain number of micron-sized clusters in silica gel. According to the insignificant differences in the number, size and dispersion of the cluster particles, their dispersion was comprehensively judged and ranked from high to low as follows: NPCC2>NPCC4>NPCC1>NPCC3.

[0046] The data of the above examples are sorted out, and the data obtained in Example 1 are shown in the following table: Table 2: Data obtained in Example 1 The data obtained in Example 2 are shown in the following table: Table 3: Data obtained in Example 2 Comparing Example 1 and Example 2, it can be seen that the adsorption and dispersion behaviors of nano-calcium carbonate powder on the interface of silica gel and polyethylene are significantly different. The difference in dispersibility between NPCC1 and NPCC2 is significantly amplified at the polyethylene interface. The difference in dispersion rate between the two on the silica gel interface is 7.5% (0.129 and 0.120), while this value surges to 65.9% (0.170 and 0.107) on the polyethylene interface. This shows that NPCC1, which has a relatively small specific surface area, is easier to disperse in a non-polar system represented by polyethylene than NPCC2. At the same time, by comparison, it can be seen that the evaluation of the dispersibility of nano-calcium carbonate powder must correspond to the dispersion medium.

[0047] In Example 3, compared with Example 1, the pulse spraying time was shortened from 45ms to 30ms, and the initial particle size of the same nano-calcium carbonate sample NPCC2 adsorbed and dispersed on the silica gel interface was reduced from 25.44μm to 20.88μm, and the dispersion rate was increased from 0.120μm / s to 0.131μm / s. This shows that shortening the spraying time helps to inhibit the formation and growth of nano-calcium carbonate particle clusters, but from the microscopic picture, the particles adsorbed on the interface are significantly reduced, and the effective measurement points that can be observed are reduced, which affects the representativeness of the observation.

[0048] In Example 4, compared with Example 2, the ultrasonic dispersion time was increased from 45s to 50s, and the particle size of the same nano-calcium carbonate sample NPCC2 after dispersion on the polyethylene interface was reduced from 21.24μm to 20.76μm, and the dispersion rate increased almost unchanged (0.107μm / s to 0.106μm / s). This shows that the cluster structure of NPCC2 with a relatively high specific surface area is relatively stable on the polyethylene interface, and it is difficult to break this stable state by extending the ultrasonic time, and the dispersion state of the nano-calcium carbonate particles has not changed substantially.

[0049] The fineness of the calcium nanocarbonate in Comparative Example 1, i.e. the scratch position, is difficult to accurately judge, especially for samples with discontinuous point scratches or small differences, such as NPPC3 and NPCC4, where the scratches are almost at the same position, and subjective judgment based on experience is required.

[0050] The test results of Comparative Example 2 are the size of nano-calcium carbonate particles measured in an extremely dilute solid-liquid phase system. There is a lack of theoretical basis for characterizing dispersibility by particle size, and there are also objections to the correspondence between its dispersion medium, operation and application scenarios.

[0051] In the electron microscopy method of comparative example 3, it is difficult to unify the dispersion conditions when preparing the sample of the powder to be tested, and the observation field is small and the representativeness is low, so the observer is prone to make a biased conclusion; the detection cost is high, the operation is complicated and the timeliness is poor.

[0052] Although the method of Comparative Example 4 is close to production, it only qualitatively judges the dispersibility based on the size and discreteness of the nano-calcium carbonate particles after dispersion in the medium, and has the limitation of measuring dynamic performance with static indicators.

[0053] From the analysis results of the examples and comparative examples, it can be seen that only the examples can obtain results that are consistent with both theoretical expectations and production practice experience: that is, NPCC1>NPCC2>NPCC3>NPCC4. This is because the above four nano-calcium carbonate samples are prepared using the same raw materials and the same process. The higher the specific surface area, the greater its surface energy and agglomeration tendency, and the relatively poorer the dispersion performance. The mechanical properties of nano-calcium carbonate filled silicone rubber in Table 4 also show that the actual application performance NPCC1>NPCC2>NPCC3>NPCC4, which fully reflects the importance of dispersion. Silicone glue sample Filled with calcium nanocarbonate (55%) Tensile strength MPa Elongation at break 100% RTV-1 NPCC1 2.65 3.60 RTV-2 NPCC2 2.52 3.53 RTV-3 NPCC3 2.41 3.46 RTV-4 NPCC4 2.49 3.13

[0054] Table 4: Performance comparison of various types of samples of calcium nanocarbonate filled silicone rubber products However, all the comparative proportions reached conclusions inconsistent with this, indicating that they all have their own limitations.

[0055] In summary, the nano-calcium carbonate dispersibility analysis and evaluation method of the present invention can stably, efficiently and quantitatively analyze the dispersibility of nano-calcium carbonate under conditions close to actual application scenarios, and has significant technical characteristics of visualization, quantification and dynamics. Compared with existing methods, it has higher resolution and test accuracy, which is of great practical significance for effectively guiding the production and research activities of the upstream and downstream industries of nano-calcium carbonate.

Claims

1. A dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder, characterized in that: The steps include: A, fix the carrier membrane on the slide; B, mixing the nano calcium carbonate powder to be tested in a fluid and spraying the mixture on the carrier film; C, subjecting the carrier film and the glass slide to ultrasonic vibration treatment together; D. Use a microscope to observe the distribution state of nano-calcium carbonate powder on the carrier membrane before and after ultrasonic treatment, and capture stable imaging pictures; E, using a computer processing program to process the image obtained in step D, marking representative nano-calcium particles or clusters, counting their geometric dimensions (maximum dimensions), and obtaining the average geometric dimensions D0 and Dt respectively; F, calculate the dispersion rate of nano calcium powder (Dt-D0) / t to evaluate its dispersion performance.

2. A dynamic microscopic analysis method for evaluating the dispersibility of nano calcium carbonate powder according to claim 1, characterized in that: In step B, a fluidizing device is used, and the fluid is compressed air.

3. A dynamic microscopic analysis method for evaluating the dispersion performance of nano calcium carbonate powder according to claim 2, characterized in that: The spraying direction of the fluidization device is perpendicular to the plane where the glass slide is located.

4. A dynamic microscopic analysis method for evaluating the dispersion performance of nano calcium carbonate powder according to claim 2 or 3, characterized in that, The nozzle pressure of the fluidization device is 1-3MPa, the flow rate is 4-6L / min, the initial velocity is 10-15 m / s; the distance between the nozzle and the glass slide is 5-10mm.

5. A dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder according to claim 2 or 3, characterized in that: The fluidization device adopts pulse spraying mode, and the pulse spraying time is 30 to 50 ms.

6. A dynamic microscopic analysis method for evaluating the dispersion performance of nano-calcium carbonate powder according to claim 1, 2 or 3, characterized in that: In step C, the carrier film and the glass slide are horizontally placed in a sample boat, and the sample boat floats on the surface of the medium water in the ultrasonic generator.

7. A dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder according to claim 6, characterized in that: The ultrasonic treatment time is 30-60s.

8. A dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder according to claim 1, 2 or 3, characterized in that: The carrier membrane material is determined by the polarity of the downstream application system.

9. A dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder according to claim 8, characterized in that: The carrier film is a silicone film or a polyethylene film.

10. A dynamic microscopic analysis method for evaluating the dispersibility of nano-calcium carbonate powder according to claim 1, 2 or 3, characterized in that: The carrier film and the glass slide are bonded together with DOP.

Citation Information

Patent Citations

  • Double-groove scraper fineness meter and method for detecting covering power of titanium dioxide in coating by using double-groove scraper fineness meter

    CN118670935A

  • Fluidization device for homogenizing nano calcium carbonate powder

    CN216987991U